Effect of intercalating agents on structure and properties of dimer acid‐based polyamide modified by in situ doping of Na‐montmorillonite. (14th July 2016) - Wang, Xiaohui
Abstract : Under the condition of 0.4% (mass), the effects of intercalating agents on conglomeration structure and thermal and mechanical properties of dimer acid‐based polyamide (DAPA) were investigated. The results show that layer‐stripped Na‐montmorillonite (MMT) with octadecyl trimethyl ammonium chloride caused a sharp decrease of content of the γ crystal phase in DAPA, thus bringing out decrease in mechanical properties and increase in IZOD notched impact strength while a sharp increase of content with the γ crystal phase in DAPA modified by Na‐MMT with dioctadecyl dimethyl ammonium chloride. Thus, it brought out a large increase in mechanical properties and a limited increase in IZOD notched impact strength. The decomposition reaction processes of DAPA modified by Na‐MMT and Na‐MMT with octadecyl trimethyl ammonium chloride were one step ranging from 410 to 500°C, respectively. The thermal decomposition reaction processes of DAPA modified by Na‐MMT with dioctadecyl dimethyl ammonium chloride were two steps. Copyright © 2016 John Wiley & Sons, Ltd.